Phylogenetic relationships and climate-driven range shifts of Lemnaceae in South Africa - Ndou, Unarine Honest; Tshabalala, Thulani; Mankga, Ledile Thabitha; Bezeng, Bezeng Simeon (Frontiers in Ecology and Evolution, 2026)
Duckweeds (Lemnaceae) are among the smallest flowering plants with ecologically significant components of freshwater ecosystems, yet their extreme morphological reduction complicates species identification, biogeographic classification, and invasion assessments. This study integrates multi-locus molecular phylogenetics and species distribution modeling (SDM) to clarify the evolutionary relationships, native versus non-native status, and climate-driven range dynamics of duckweed species in South Africa. Phylogenetic reconstruction based on five plastid markers (matK, rbcL, rpl16, trnK-3′, and trnK-5′) resolved two well-supported subfamilies (Lemnoideae and Wolffioideae) and confirmed the monophyly of the genera Lemna, Landoltia, Spirodela, Wolffia, and Wolffiella. Of the 38 taxa analysed, nine were identified as native and 29 as non-native, providing new evidence that Lemna minor and Lemna gibba, previously regarded as invasive in South Africa, are native species. Ecological niche models developed using MaxEnt and bioclimatic variables projected current and future habitat suitability under four Shared Socioeconomic Pathways (SSP1-2.6, SSP2-4.5, SSP3-7.0, SSP5-8.5) across three global climate models (MIROC6, EC-Earth3-Veg, and UKESM1-0-LL). Current suitability was found to be the highest in the coastal provinces (KwaZulu-Natal, Eastern Cape, and Western Cape). Future projections revealed model-dependent outcomes, with MIROC6 and EC-Earth3-Veg predicting net expansion of climatically suitable habitat, particularly in inland provinces such as Mpumalanga, Limpopo, North-West, and Gauteng while UKESM1-0-LL consistently predicts contraction. The congruence between phylogenetic identity and projected range shifts highlights regions and freshwater systems vulnerable to future duckweed invasions. By integrating evolutionary history with climate projections, this study provides a robust framework for refining invasive species management, conserving native freshwater flora, and guiding adaptive conservation planning under climate change in South Africa.